2023
DOI: 10.1007/s11010-023-04818-9
|View full text |Cite
|
Sign up to set email alerts
|

The role and intervention of mitochondrial metabolism in osteoarthritis

Abstract: Osteoarthritis (OA), a prevalent degenerative joint disease, affects a substantial global population. Despite the elusive etiology of OA, recent investigations have implicated mitochondrial dysfunction as a significant factor in disease pathogenesis. Mitochondria, pivotal cellular organelles accountable for energy production, exert essential roles in cellular metabolism. Hence, mitochondrial dysfunction can exert broad-ranging effects on various cellular processes implicated in OA development. This comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Mitochondrial function could represent a target for OA treatment ( 17 ). Mao et al reviewed mitochondrial dysfunctions in OA chondrocytes reported as decreased ATP production, increased oxidative stress, calcium dysregulation, increased permeability of the mitochondrial membrane, mtDNA alternations, and activation of mitochondrial apoptotic pathway resulting in cartilage degeneration.…”
mentioning
confidence: 99%
“…Mitochondrial function could represent a target for OA treatment ( 17 ). Mao et al reviewed mitochondrial dysfunctions in OA chondrocytes reported as decreased ATP production, increased oxidative stress, calcium dysregulation, increased permeability of the mitochondrial membrane, mtDNA alternations, and activation of mitochondrial apoptotic pathway resulting in cartilage degeneration.…”
mentioning
confidence: 99%